2010
DOI: 10.1371/journal.pone.0012242
|View full text |Cite
|
Sign up to set email alerts
|

Continued Decline of Malaria in The Gambia with Implications for Elimination

Abstract: BackgroundA substantial decline in malaria was reported to have occurred over several years until 2007 in the western part of The Gambia, encouraging consideration of future elimination in this previously highly endemic region. Scale up of interventions has since increased with support from the Global Fund and other donors.Methodology/Principal FindingsWe continued to examine laboratory records at four health facilities previously studied and investigated six additional facilities for a 7 year period, adding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
135
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(143 citation statements)
references
References 30 publications
8
135
0
Order By: Relevance
“…Tenth, findings from other studies in countries such as The Gambia suggest substantial decreases in malaria in these settings; in our analysis of mortality, however, these types of studies have not been used. 158,159 Eleventh, our analysis of tuberculosis assumes that local expert judgment about the case-detection rate is unbiased; this assumption, however, might be incorrect for countries with higher or lower case-detection rates. Twelfth, our uncertainty intervals for tuberculosis incidence and prevalence generated from DisMod-MR 2.0 are probably underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Tenth, findings from other studies in countries such as The Gambia suggest substantial decreases in malaria in these settings; in our analysis of mortality, however, these types of studies have not been used. 158,159 Eleventh, our analysis of tuberculosis assumes that local expert judgment about the case-detection rate is unbiased; this assumption, however, might be incorrect for countries with higher or lower case-detection rates. Twelfth, our uncertainty intervals for tuberculosis incidence and prevalence generated from DisMod-MR 2.0 are probably underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Currently SCR is not sensitive to short term changes in transmission since antibodies can persist for years after the period of exposure, so it is necessary to wait for the population to age (Corran et al, 2007). However some studies have reported SCR in the youngest children (<5 years) (Ceesay et al, 2010) and this is a method for making SCR estimates more useful for determining recent yearly reductions in transmission intensity. Antigens that prove useful components of malaria vaccines may become redundant in SCR assays if such a vaccine becomes widely used (Corran et al, 2007).…”
Section: Accuracy Precision and Costs Of Malaria Metricsmentioning
confidence: 99%
“…However, numbers of febrile illness have not reduced and may still be considered malaria in the absence of diagnosis to differentiate malaria from other pyrogenic agents [8]. For example, during the 2008 malaria season in Farafenni area in The Gambia, only 11% (24/223) of febrile episodes detected during a 22-week follow-up of a cohort of 800 children were due to malaria [11]. Other causes of febrile illness include invasive bacterial infections such as typhoid fever and emerging or neglected zoonoses such as leptospirosis, Q fever, tick-borne relapsing fever and brucellosis [1215].…”
Section: Introductionmentioning
confidence: 99%